Basalt Handaxes: Preliminarily Testing the Lithic Translation Strategy Hypothesis and Comparisons with the Fontana Ranuccio Site Bifacial Tools - Giorgio Chelidonio (EXARC, 2019)
The oldest bifacial “handaxes” known so far belong to the “Kokiselei 4” site, dated to 1.76 Ma (West Turkana, Kenya; Texier, 2018). They have been manufactured by direct lithic percussion on magmatic effusive stone materials. Considering that the evolution of “fully operational intelligence” (Wynn, 1979) has been associated with the so-called “Mode 2” chaîne opératoire, it seems interesting to verify the potential adaptive meaning of selecting scarcely isotropic stones. This techno-behavioural approach, somehow similar to the so-called “lithic translation strategy” (Chelidonio, 1997), is a preliminary hypothesis that could be applied to the Fontana Ranuccio handaxes (458 ka BP, Latium/central Italy). In this very peculiar Acheulean assemblage, a few bifacial tools were manufactured using local “lava”1 (Biddittu, 1993, p. 58); others were roughly manufactured by flaking off thick elephant bones (Pereira et al., 2018). The above hypothesis has been preliminarily tested by experimenting the “Mode 2” techno-evolutionary step on some basalt samples at my disposal, to verify symmetrical flaking results applied to non-vitreous or non-cherty stones. Obviously, it is advisable to perform future tests on the basalt-like material available in the Fontana Ranuccio area, to adequately assess the techno-behavioural meaning of this peculiar lithic assemblage.